Inexpensive and green electrochemical sensor for the determination of Cd(II) and Pb(II) by square wave anodic stripping voltammetry in bivalve mollusks. (15th August 2020) - Pizarro, Jaime; Segura, Rodrigo; Tapia, Diego; Navarro, Freddy; Fuenzalida, Francesca; Jesús Aguirre, María
Highlights: Graphene quantum dots-Nafion-Glassy carbon electrode is proposed for Cd(II) and Pb(II) detection. Graphene quantum dots-Nafion improves preconcentration and sensitivity for Cd(II) and Pb(II) determination. The modified electrode was applied in the determination of Cd(II) and Pb(II) in bivalve mollusks samples. Abstract: An inexpensive and environmental friendly electrochemical sensor based on a glassy carbon electrode (GC) modified with graphene quantum dots (GQDs) and Nafion (NF) has been developed for the determination of Cd(II) and Pb(II) in bivalve mollusks using square wave anodic stripping voltammetry (SWASV). GQDs were characterized by UV–Vis spectroscopy, fluorescence and transmission electronic microscopy (TEM). The modified electrode was evaluated by cyclic voltammetry, scanning electronic microscopy (SEM) and electrochemical impedance spectroscopy (EIS). A linearity of 20–200 μg L −1 was found, with a limit of detection (LOD) of 11.30 μg L −1 for Cd(II) and 8.49 μg L −1 for Pb(II). The proposed methodology was validated with a certified reference material TMDA-64.2. The reproducibility of GC/GQDs-NF for both species had an RSD of less than 10%. The results were compared with ICP-OES. The method was applied in the determination of Cd(II) and Pb(II) in bivalve mollusks samples with excellent results.